Corrigenda and Addenda to the Article “The taxonomic history of Indo-Papuan groundsnakes, genus Stegonotus Duméril et al., 1854 (Colubridae), with some taxonomic revisions and the designation of a neotype for S. parvus (Meyer, 1874)” by Kaiser et al. (2018) - Kaiser, Christine M.; O’shea, Mark; Kaiser, Hinrich (Zootaxa, 2019)
Kaiser et al. (2018) recently presented a comprehensive history of snakes in the genus Stegonotus Duméril et al., 1854 that included substantial taxonomic revisions. Given the scope and production of this work a few issues remained uncorrected during several proof stages, which we correct herein. Furthermore, after the paper was published some relevant information emerged that we do not want to leave unexposed, and which we hereby add to our discussion.